A predictive model of overstrength due to strain hardening in steel EBF links - PrakashVemuri, Jaya (Journal of Structural Engineering, 2024)
Steel Eccentrically Braced Frames (EBFs) have been used in earthquake prone areas due to their ability to confine damage to the links, which can be easily replaced after damage. EBFs are designed using Capacity Based Design, and for economical design, it is essential that the designer can estimate the strength of link accurately. In this paper, a model to estimate overstrength due to strain hardening in steel EBF links is presented. A regression analysis is performed on experimental link data obtained from literature. The normalized link length, link rotation, normalized stiffener spacing and the ratio of ultimate strength to yield strength are observed to affect link overstrength. A good fit is obtained between the calculated values from the model and the actual experimental values. The parameter estimates and their errors are tabulated and are found to be statistically significant. The residual analysis carried out on the independent parameters shows no trends. The proposed model may be used to replace code-suggested overstrength values.